Distribution of Different Forms of Soil Acidity in Selective Laterite Soils under Cashew Plantations in Coastal Karnataka - Srinivasan, R.; Natarajan, A.; kumar, K. S. Anil; Dharumarajan, S.; Kalaivanan, D. (International Journal of Bio-resource and Stress Management, 2023)
A study was conducted to examine soil morphological, physico-chemical properties and different forms of soil acidity of six selected laterite soils under cashew plantations in coastal Karnataka. Pedons were dug to a depth of 2 m at six selected locations viz. Pala hillock, DCR-Shanthigodu, Muchipadavu, Mulia, ARS-Ullal and Palikudel and horizon wise samples were collected to study the various soil parameters including different forms of soil acidity. Cation exchange capacity and base saturation of the soils were varied from 7.60 to 19.8 cmol (p+) kg-1 and 4 to 32%, respectively. The exchangeable acidity varied from 0.06 to 2.20 cmol (p+) kg-1 and extractable acidity ranged from 8.16 to 47.89 cmol (p+) kg–1. Presence of low exchangeable acidity could be due to efficient recycling of basic cations and higher exchangeable acidity in few locations may be due to the presence of exchangeable ions like H+ and Al3+. Results obtained from this study indicated that the Pedons 1, 4, 5 and 6 requires more lime than others to reclaim for maximizing cashew production by restoring the available soil nutrients.